2010
DOI: 10.1021/ma101663x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polystyrenes−Poly(alkyl methacrylates) Block Copolymers via Anionic Polymerization Using an Integrated Flow Microreactor System

Abstract: The polystyrene living polymer end, which was produced by butyllithium initiated anionic polymerization of styrene in a flow microreactor system was found to be effectively trapped with 1,1-diphenylethylene. The resulting organolithium species could be used as a macro initiator for anionic polymerization of alkyl methacrylates to obtain styrene−alkyl methacrylate diblock copolymers using an integrated flow microreactor system. A high level of control of molecular weight was achieved at easily accessible temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 114 publications
1
36
0
Order By: Relevance
“…The introduction of different functional groups into the polymer greatly enhances its practical applications in biodiagnosis, separation media and therapeutics [1][2][3]. The selection of monomers depends on their intended applications.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of different functional groups into the polymer greatly enhances its practical applications in biodiagnosis, separation media and therapeutics [1][2][3]. The selection of monomers depends on their intended applications.…”
Section: Introductionmentioning
confidence: 99%
“…25,[32][33][34] Nagaki et al demonstrated block copolymerizations of styrene and alkyl methacrylate (M n : 3,900-17,000 g·mol -1 , M w /M n : 1.1-1.5) in THF using an integrated flow micro reactor system consisting of syringe pumps and three T-shaped mixing elements. 20 The polystyrene end groups were capped with DPE within 3 s with high capping efficiency (81% at 0 o C) using the flow micro reactor system.…”
Section: Homopolymerization Of Methyl Methacrylate and 2-vinylpyridinmentioning
confidence: 99%
“…14 Many studies on anionic polymerizations of styrene, styrene derivatives, and alkyl methacrylate to homopolymers and block copolymers in THF have been performed using flow reactors. [15][16][17][18][19][20][21] In particular, Yoshida & Nagaki et al demonstrated anionic block copolymerization (M n 16,900 g·mol -1 ) of styrene and alkyl methacrylate using a micro flow reactor. 16 For practical applications in the industrial field, such as anti-reflective coating materials and nano-patterning in PSb-PMMA, block copolymers with molecular weights greater than 100×10 3 g·mol -1 are necessary to be produced in large scale.…”
Section: Introductionmentioning
confidence: 99%
“…With the need to suppress such side reactions, anionic polymerization of methacrylates has been more difficult than anionic polymerization of styrenes [11,12]. The flow microreactor system allows anionic polymerization of methacrylates under the conditions that are easily accessible in industrial production (−30°C or above) [13][14][15].…”
Section: Flash Anionic Polymerizationmentioning
confidence: 99%